Enzalutamide versus flutamide for castration-resistant prostate cancer after combined androgen blockade therapy with bicalutamide: the OCUU-CRPC study - Iguchi, Taro; Tamada, Satoshi; Kato, Minoru; Yasuda, Sayaka; Machida, Yuichi; Ohmachi, Tetsuji; Ishii, Keiichi; Iwata, Hiroyuki; Yamamoto, Shinji; Kanamaru, Tomohiro; Morimoto, Kazuya; Hase, Taro; et al. (International journal of clinical oncology, 2020)
Background Before the androgen target therapy era, flutamide was widely used for castration-resistant prostate cancer in Japan. Enzalutamide is currently the recommended treatment; however, the efficacy and safety of enzalutamide and flutamide after combined androgen blockade therapy with bicalutamide, has not been compared. Methods Patients with castration-resistant prostate cancer who received combined androgen blockade therapy with bicalutamide were randomly assigned to receive either enzalutamide or flutamide. The primary endpoint for efficacy was the 3-month prostate-specific antigen response rate. This trial is registered with ClinicalTrials.gov (NCT02346578) and the University hospital Medical Information Network (UMIN000016301). Results Overall, 103 patients were enrolled. The 3- (80.8% vs. 35.3%; p < 0.001) and 6-month (73.1% vs. 31.4%; p < 0.001) prostate-specific antigen response rates were higher in the enzalutamide than in the flutamide group. The 3-month disease progression rates (radiographic or prostate-specific antigen progression) were 6.4% and 38.8% in the enzalutamide and flutamide groups, respectively [hazard ratio (HR): 0.16; 95% confidence interval (CI): 0.05–0.47; p < 0.001]; the 6-month rates were 11.4% and 51.1%, respectively (HR 0.22; 95% CI 0.09–0.50; p < 0.001). Enzalutamide provided superior prostate-specific antigen progression-free survival compared with flutamide (HR 0.29; 95% CI 0.15–0.54; p < 0.001). Median time to prostate-specific antigen progression-free survival was not reached and was 6.6 months in the enzalutamide and flutamide groups, respectively. Conclusions As an alternative anti-androgen therapy in patients with castration-resistant prostate cancer who fail bicalutamide-combined androgen blockade therapy, enzalutamide provides superior clinical outcomes compared with flutamide. Enzalutamide should be preferred over flutamide in these patients.